Acquired Long QT Syndrome and Torsade de Pointes Associated with HIV Infection - Alexander Shimabukuro-Vornhagen; Jan Rybniker; Shahram Zoghi; Gerd Faetkenheuer; Guido Michels; Erland Erdmann; Michael von Bergwelt-Baildon; Matthias Kochanek (Case Reports in Medicine)
Here, we report the case of an HIV infected patient that was treated for pneumonia with a macrolid antibiotic. The patient experienced a prolongation of the already pathologic QTc interval resulting in repeated torsades de pointes necessitating CPR and implantation of an AICD. This case exemplifies that torsades de pointes due to acquired long QT syndrome is a serious and potentially fatal complication in HIV-positive patients.